APLIKASI BAKTERIN SEBAGAI IMUNOSTIMULAN UNTUK PENCEGAHAN INFEKSI VIRAL NERVOUS NECROSIS (VNN) PADA BENIH IKAN KERAPU BEBEK, Cromileptes altivelis - Des Roza; Fris Johnny (Jurnal Perikanan Universitas Gadjah Mada, 2008)
An experiment on application of immunostimulant bacterin in order to prevent Viral Nervous Necrosis (VNN) in seed production of humpback grouper, Cromileptes altivelis has been conducted in Gondol Research Institute for Mariculture hatchery. The experiment arranged in completely randomized design with two replicates. One thousand and five hundred fry with total length 4 cm were treated as followed ; 1 ml bacterin/L sea water by immersion (Treatment A), 1 ml bacterin/kg pellet by oraly (Treatment B), and without bacterin as a control (C). Bacterin was immersion and oraly every 10 days for 60 days rearing period. Challenge test with VNN was carry out at day 30 and 60. At the end of experiment the non-spesific immune were examined. Result of challenge test performed at day 30 showed that treated fish gave positive response to bacterin treatment. The highest survival showed by treatment B (65.0%) followed by treatment A(50.0%) and C (22.5%). The same result also showed after challenge test at day 60. The highest survival was 72.5% (treatment B) followed by 67.5% (treatment A) and 35.0% (control). Phagocytic activity (PA) of treatment B was 15.5%, and 14.0% from treatment A compared to 8.0% in control. Lysozyme activity (LA) of treated groups were also higher than control namely 1.8 cm for treatment B followed by 1.6 cm for treatment A, and only 1.2 cm in control. Addition of bacterin immunostimulant in feed gives is survival rate higher compared to way of immersion and control. Statistically non-spesific immune response of humpback grouper was significant different among treatment (P<0,05).